Comparation Between Mac conkey and Coconut Water Medium as a Growth Medium for Escherichia coli - Endah Prayekti; Suliati Suliati; Dwi Agustin Wulandari (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2021)
Escherichia coli is the bacteria that can cause diarrhea in humans and often used as a parameter of stool environmental pollution. Culture of E. coli from the sample often requires Mac Conkey as commercial media which is able to distinguish it from other bacteria in the Enterobacteriaceae group. Commercial media such as Mac Conkey certainly has a price that is quite expensive because of its ability as a growth medium for Enterobacteriaceae. Therefore, in the study tested natural ingredients that can be used for growth media, such as coconut water. The purpose of this study was to compare the ability of Mac Conkey media and coconut water to support the growth of E. coli. This research is an experimental study with a completely randomized design. The concentration of coconut water tested was 0%, 20%, 40%, 60%, 80%, and 100%. The results showed that at the concentration of coconut water 20% to 60% the number of E. coli colonies on coconut water media was slightly below the Mac Conkey Agar media, while in coconut water a concentration of 80% showed a greater number of colonies than Mac Conkey. The Mann Whitney test showed a significant difference between the number of colonies on 80% coconut water media and Mac Conkey Agar, which was equal to 0.004 (p < 0.05). Based on these results, coconut water has the potential to be used as a growth medium for E. coli.